2020
DOI: 10.5603/mrj.a2020.0009
|View full text |Cite
|
Sign up to set email alerts
|

Does morphine remain a standard of care in acute myocardial infarction?

Abstract: Morphine is routinely used for pain relief in patients with acute myocardial infarction. However, it was documented that morphine decreases the bioavailability and antiplatelet effect of P2Y 12 receptor inhibitors. Multiple strategies to overcome this undesirable interaction are currently under investigation; they include the following: administration of crushed ticagrelor tablets, co-administration of metoclopramide, bridging with intravenous antiplatelet agents, or replacement of morphine with other analgesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Nevertheless, morphine may cause adverse effects, including bradycardia, hypotension, and impairment of the intestinal propulsive function or even suppression of the respiratory function [17]. Additionally, morphine leads to impaired absorption of orally administered antiplatelet drugs, delay of anti-aggregatory effect and its reduction [18]. Noteworthy, this issue not only concerns clopidogrel, but also the newer P2Y12 receptor antagonists prasugrel and ticagrelor [19][20][21].…”
Section: Chest Pain Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, morphine may cause adverse effects, including bradycardia, hypotension, and impairment of the intestinal propulsive function or even suppression of the respiratory function [17]. Additionally, morphine leads to impaired absorption of orally administered antiplatelet drugs, delay of anti-aggregatory effect and its reduction [18]. Noteworthy, this issue not only concerns clopidogrel, but also the newer P2Y12 receptor antagonists prasugrel and ticagrelor [19][20][21].…”
Section: Chest Pain Managementmentioning
confidence: 99%
“…According to the 2020 ESC guidelines, potent P2Y12 receptor inhibitors (ticagrelor or prasugrel) exhibit a fast onset of antiplatelet action, thereby allowing loading dose administration after diagnostic coronary angiography and directly before PCI [5]. However, the fast onset of action has been shown only in a stable setting [66][67][68][69], while in patients with MI the antiplatelet effect of both drugs was delayed, achieving satisfactory platelet inhibition in the majority of patients 2 hours after loading dose administration [17,18,70,71]. Of note, even 4 hours after administration of the loading dose of ticagrelor high platelet reactivity (as assessed with VASP assay) was found in 7-37% of patients (depending on concomitant morphine administration) [17,18,70,71].…”
Section: Platelet P2y12 Receptor Inhibitors In the Treatment Of Patie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on available data, the latest European Society of Cardiology (ESC) guidelines on the management of acute ST-segment elevation myocardial infarction patients reduced the class of recommendation of titrated opioid use to IIa [7]. Despite this, morphine is still a standard analgesic treatment in ACS patients and it should not be routinely withdrawn [8][9][10]. Based on available research, morphine, acting via µ-opioid receptors, was found to inhibit gastrointestinal motility or induce adverse effects such as nausea or vomiting [11].…”
Section: Introductionmentioning
confidence: 99%
“…Blood tests using nonanticoagulated (native) blood and inducing thrombus formation solely by shear forces were developed in 1970 [ 14–21 ]. Recently, a commercially available point-of-care thrombosis test was shown to have pathological relevance to human arterial thrombosis [ 22–40 ].…”
mentioning
confidence: 99%